Highlighting the Neuropsychological Consequences of COVID-19: Evidence From a Narrative Review - Kalliopi Megari PhD; Evanthia Thomaidou MD, PhD; Electra Chatzidimitriou MSc (SAGE Publishing, 2024)
The coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus-2, although largely affecting the respiratory system, commonly presents with numerous clinical symptoms from other systems. COVID-19 has been associated with both acute and persistent neurological abnormalities in a substantial proportion of patients. Notably, post-COVID-19 neuropsychological abnormalities have garnered attention, highlighting a high prevalence of neurocognitive issues in affected individuals. This narrative review synthesizes current knowledge on the neuropsychological impact of COVID-19, drawing insights from an extensive online search of published literature conducted in the PubMed (MEDLINE) and Scopus databases. The findings underscore significant neuropsychological effects of COVID-19 observed at both individual and societal levels during the ongoing pandemic. Neuropsychological deficits such as memory difficulties, attention problems, and executive dysfunction, alongside physical symptoms like headaches and fatigue were commonly reported. Additionally, psychological challenges, including fear, anxiety, and depression, emerged as prevalent issues arising from the uncertainties surrounding the situation, social isolation, and employment insecurities. The identified neuropsychological manifestations of COVID-19 can significantly impede normal cognitive and emotional functioning, potentially resulting in decreased productivity and an overall decline in mental health and quality of life. Early identification of signs indicative of neurological or psychological decline becomes imperative, offering a crucial opportunity to mitigate the risk of long-term neuropsychological dysfunction through the development of targeted interventions.